Roberto Mange, the creation of the Railroad Center for Professional Education and Selection (CFESP) and training for work in the 1930s and 1940s (Research, Society and Development, 2021)
The objective of this article is to explain the articulations that involved Roberto Mange and the creation and functioning of the Railway Center for Professional Education and Selection (CFESP), created in 1934, to train and select railway workers. The research is part of the field of the History of Professional Education and is justified by the importance of CFESP for the qualification and rationality of the training of railway workers, in addition to having originated other Railway Education and Professional Selection Centers in Brazil. The methodology used was documentary and bibliographic research through authors such as Zanetti (2001), Fonseca (1961); Cunha (2000), Pedrosa (2014), Ciavatta (2009), dissertations and theses. Roberto Mange's professional trajectory is related to the creation, in 1923, of the Practical Mechanics course at the School of Arts and Crafts of São Paulo; with the creation of the Escola Profissional Mecânica, in 1924; with the creation of the Sorocabana Teaching Service and Professional Selection Railway Course and the creation of the Rational Work Organization Institute (IDORT), both in 1931; and finally, the creation of the CFESP aimed at training railway workers in São Paulo and other Brazilian states. We conclude that the analysis presented elements that corroborate the argumentation about the role of engineer Mange in actions related to the rationalization of work and application of scientific management methods, favoring cooperation between the railways and public authorities.